2021
DOI: 10.1051/e3sconf/202124613001
|View full text |Cite
|
Sign up to set email alerts
|

Primary Energy Balance driven Integrated Energy Design Process of Positive Energy Building

Abstract: The ISO 52000–1:2017 is the overarching Energy Performance of Buildings (EPB) standard, providing the general framework of the EPB assessment. It is applicable to the assessment of overall energy use of a building, by measurement or calculation, and the calculation of energy performance in terms of primary energy or other energy-related metrics. ISO 52000–1 provides general profound guidelines, but also gives the freedom to adapt the guidelines with national standards and regulations. This article focuses on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The authors identified 82 papers that fit the eligibility criteria of the study. Here, only the studies that present comprehensive investigations to achieve plus energy building under the Mediterranean climatic conditions are considered [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. It is worth noting that studies that did not achieve plus energy balance are not considered in the analysis, such as [26][27][28][29][30][31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors identified 82 papers that fit the eligibility criteria of the study. Here, only the studies that present comprehensive investigations to achieve plus energy building under the Mediterranean climatic conditions are considered [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. It is worth noting that studies that did not achieve plus energy balance are not considered in the analysis, such as [26][27][28][29][30][31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The design of the building follows an integral design process to achieve a positive energy building, with local energy production from photovoltaic panels, which are placed both on north-west and south-east block roof. Details about the final building design can be found in Tamm et al (2021).…”
Section: Case Stutymentioning
confidence: 99%